Geography, trade, and internal migration in China - MA, Lin (Institutional Knowledge at Singapore Management University, 2020)
This paper quantitatively studies the local welfare impacts of inter-city migration in China. We structurally estimate a trade model with endogenous migration decisions using data from 279 prefecture-level cities. The results suggest that inflows of migrant workers increase welfare in the destination cities between 2000 and 2005 despite their negative impacts on congestion and nominal wage. The positive local impacts of migration depend crucially on the endogenous firm entry. The positive impacts in the destination cities also spill over to the neighboring cities through inter-city trade, often leading to higher welfare gains in the nearby cities than the destination cities themselves. We also show that further relaxing the Hukou restrictions in the largest Chinese cities is welfare-improving to the local residents.